The role of wave-exposure and human impacts in regulating the distribution of alternative habitats on NW Mediterranean rocky reefs. (5th February 2018) - Bulleri, Fabio; Cucco, Andrea; Dal Bello, Martina; Maggi, Elena; Ravaglioli, Chiara; Benedetti-Cecchi, Lisandro
Abstract: The global decline of canopy-forming macroalgae has stimulated research on the mechanism regulating shifts among alternative habitats on rocky reefs. The effects of sea urchin grazing and alterations of environmental conditions are now acknowledged as the main drivers of shifts between canopy-formers and encrusting coralline barrens and algal turfs, respectively. The conditions under which these mechanisms operate remains, however, somewhat elusive. This is mostly a consequence of the fact that our current understanding has been generated by envisioning habitat shifts as dichotomic, at odds with rocky reef landscapes being composed by mosaics of habitats and with evidence of strong interactions among the species that compose each of the alternative habitats. Using data from a long-term sampling program and path analysis, we investigated how wave-exposure and human-induced degradation of environmental conditions regulate the mechanisms maintaining algal canopies formed by Cystoseira crinita, barren habitats and algal turfs as alternative states on subtidal reefs in the NW Mediterranean. In the Tuscan Archipelago, wave-exposure had positive effects on sea urchins, which, likely due to their low mean density, had weak effects on each of the alternative habitats. Canopy-forming macroalgae resulted, instead, to exert strong negative effects on the abundance of algal turfs. Since data from the Tuscan Archipelago did not explain any of the variation in the abundance of C. crinita canopies, a further analysis was performed including data from the coast of Tuscany to assess the role of cumulative human impacts in regulating habitat shifts. This showed that degradation of environmental conditions is a direct cause of the decline of macroalgal canopies, indirectly favouring the dominance of algal turfs. Our study suggests that management of human impacts should be considered a priority for preserving subtidal canopies formed by Cystoseira in the NW Mediterranean and that conservation efforts based exclusively on the control of sea urchin populations might be doomed to failure in some areas.